Disturbance and repair of solitary waves in blood vessels with aneurysm - Noubissie, S.; Kraenkel, Roberto André [UNESP]; Woafo, P. (Elsevier B.V., 2009)
This paper analyzes the effects of a local increase of radius followed by local variation of the thickness or rigidity of an elastic tube on the behavior of solitary waves. The basic equations for the analysis is a set of Boussinesq-type equations derived from the flow equations in elastic tubes. It is found that the increase in rigidity and thickness reduces the effects of the tube local enlargement on the amplitude of waves. Attention is paid to the aneurysmal affection of blood vessels where there is an increase in rigidity due to calcification or ail increase of thickness due to thromboses. It thus comes that those effects contribute to the regeneration of blood waves and can merge the effects of the disease. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: blood solitary waves; Boussinesq equations; aneurysm disturbance; repair of blood waves